beta(2)-Agonists and cAMP inhibit protein degradation in isolated chick (Gallus domesticus) skeletal muscle - Navegantes, LCC; Machado, C. R.; Resano, NMZ; Migliorini, R. H.; Kettelhut, I. C. (Carfax Publishing, 2003)
1. The role of beta(2)-agonist and of cAMP in chick skeletal muscle proteolytic pathways and protein synthesis was investigated using an in vitro preparation that maintains tissue glycogen stores and metabolic activity for several hours.2. In extensor digitorum longus (EDL) muscle total proteolysis decreased by 15 to 20% in the presence of equimolar concentrations of epinephrine, clenbuterol, a selective beta(2)-agonist, or dibutyryl-cAMP. Rates of protein synthesis were not altered by clenbuterol or dibutyryl-cAMP.3. The decrease in the rate of total protein degradation induced by 10(-5) M clenbuterol was paralleled by a 44% reduction in Ca2+-dependent proteolysis, which was prevented by 10(-5) M ICI 118.551, a selective beta(2)-antagonist.4. No change was observed in the activity of the lysosomal, ATP-dependent, and ATP-independent proteolytic systems. Ca2+-dependent proteolytic activity was also reduced by 58% in the presence of 10(-4) M dibutyryl-cAMP or isobutylmethylxanthine.5. The data suggest that catecholamines exert an inhibitory control of Ca2+-dependent proteolysis in chick skeletal muscle, probably mediated by beta(2)-adrenoceptors, with the participation of a cAMP-dependent pathway.